The farm press, reform, and rural change, 1895-1920 - Fry, John J. (New York : Routledge, 2005)
An in-depth look at producers and readers of Midwestern farm newspapers at the turn of the twentieth century.
"First class papers" and "never-stop papers" -- Editors and publishers -- "What farmers read and liked" -- "Who read the agricultural journals?" -- "Innumerable little white churches" -- "The school house at the crossroads" -- "Why leave the farm?".
Includes bibliographical references (pages 211-225) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Agricultural journalism -- Middle West -- History -- 20th century; Agricultural journalism -- Middle West -- History -- 19th century; Electronic books